Interregional Differentiation of the Youth Unemployment Rate in Russia - Tatiana Blinova; Vladimir Markov; Victor Rusanovskiy (European Regional Science Association (ERSA), 2015)
The Russian labor market is not homogenous, representing a diversity of regional segments. The paper presents a statistical assessment of interregional differences in youth unemployment in Russia. The unemployment rate was decomposed into fundamental and cyclical components, which was essential for deeper understanding of the specificity of the youth labour market. We made a typology of the regions of RF according to similar trends of youth unemployment and an empirical analysis of the rates, dynamics and factors of unemployment among the young people aged 15-19 and 20-29 years for 77 regions of Russia between 2005 and 2013. We also analysed the response of the regional rates of youth unemployment to crises. For analysing the regional parameters of youth unemployment we employed economical-statistical methods. We identified the interregional differences in the youth labor market and the nature of their changes in the time of economic crisis. The statistical database for this study was the Rosstat data posted on the official website of the Federal State Statistics Service. We found that in the time of crisis the interregional differences in unemployment rates decreased and in the period of recovery growth they increased. For the 20-29-age group, the convergence was only observed between 2007 and 2009, while the other years of the period saw a divergence, which, according to the rates (the curve?s angle), was noticeably higher than that for the 15-19-age group. This can be a token of a higher economic activity of the young people aged 20-29 years. The convergence in the crisis years meant that the regions were converging to a higher unemployment rate. The divergence of the regional youth unemployment rates depicts the different rates of the recovery growth in the regions of Russia, as well as the unequal efficiency of the employment policies. The study was conducted at the Institute of Agrarian Problems of RAS with the financial support from the Russian Scientific Foundation (RSF), project # 14-18-02801.
Keywords: C51; E24; J64; 330; Russian regions; youth unemployment; modeling; interregional differences